Child and Family Characteristics Influencing Intervention Choices in Autism Spectrum Disorders. (September 2013) - Patten, Elena; Baranek, Grace T.; Watson, Linda R.; Schultz, Beth
A myriad of treatment options are available for children with autism spectrum disorders, yet little is understood regarding characteristics of parents (e.g., education) and children (e.g., severity of autism symptoms) that influence types and numbers of therapies utilized. Interviews from 70 caregivers were analyzed to determine potential influences on utilization (e.g., start of first services, use of traditional services). Only three variables predicted utilization of specific therapies: severity of sensory processing problems was associated with earlier initiation of services in general, and higher maternal and paternal education were associated with the use of dietary and/or vitamin therapy as well as with the use of a greater number of services. None of the other variables studied had predictive value, although the influence of variables not examined in this study remains to be explored.